2020
DOI: 10.3389/fimmu.2020.587014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TCR Repertoire Associated With Successful Immune Checkpoint Therapy Responses

Abstract: Immunotherapies have revolutionized cancer treatment. In particular, immune checkpoint therapy (ICT) leads to durable responses in some patients with some cancers. However, the majority of treated patients do not respond. Understanding immune mechanisms that underlie responsiveness to ICT will help identify predictive biomarkers of response and develop treatments to convert non-responding patients to responding ones. ICT primarily acts at the level of adaptive immunity. The specificity of adaptive immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 99 publications
1
50
1
Order By: Relevance
“…These are the targets of most of the immunotherapies currently being tested in clinical studies, and may function by regulating antigen-specific T cell retention and access to cancer cells, as well their function in the tumor, including local proliferation. The effect of checkpoint inhibition on TCR diversity and clonality has recently been reviewed (186), and this is an area of rapid research advancement. For example, Zhang et al demonstrated that patients exhibiting a major pathological response to PD1 inhibition showed increased sharing of highly expanded clones between the tumor, peripheral blood, and non-tumor tissue (108).…”
Section: Effect Of Checkpoint Regulators On Retentionmentioning
confidence: 99%
“…These are the targets of most of the immunotherapies currently being tested in clinical studies, and may function by regulating antigen-specific T cell retention and access to cancer cells, as well their function in the tumor, including local proliferation. The effect of checkpoint inhibition on TCR diversity and clonality has recently been reviewed (186), and this is an area of rapid research advancement. For example, Zhang et al demonstrated that patients exhibiting a major pathological response to PD1 inhibition showed increased sharing of highly expanded clones between the tumor, peripheral blood, and non-tumor tissue (108).…”
Section: Effect Of Checkpoint Regulators On Retentionmentioning
confidence: 99%
“…Given the landscape of neoantigens is heterogenous and unique for each tumor in individual patients, the clonicity and diversity of T cell repertoire to neoantigens is also unique in individual patients. As the tumor progresses, the amount and diversity of neoantigens also evolves [ 58 , 59 ]. In addition, tumor killing also releases additional neoantigens and tumor-associated antigens (TAAs) [ 58 ].…”
Section: Cancer Neoantigensmentioning
confidence: 99%
“…As the tumor progresses, the amount and diversity of neoantigens also evolves [ 58 , 59 ]. In addition, tumor killing also releases additional neoantigens and tumor-associated antigens (TAAs) [ 58 ]. The diversity of TCR repertoire increases during the evolution of tumor progression with increased neoantigens and TAAs in both TME and sentinel lymph nodes [ 54 56 ].…”
Section: Cancer Neoantigensmentioning
confidence: 99%
“…T cells are the dominant targets of immunotherapies, and their responses after immunotherapy treatments are critical to evaluate the clinical efficacy ( 108 ). Thereby, the clonal expansions and the accordant changes of TCR repertoires in tumors, normal adjacent tissue, and peripheral blood can be used for predicting the clinical responses to immunotherapies ( 109 ).…”
Section: Application Of Single-cell Omics In Tumor Immunologymentioning
confidence: 99%